Preparation method of tin dioxide nano-film

The tin dioxide nano film was synthesized by high-temperature roasting and hydrolysis using micron-scale tin dioxide powder crystals and potassium hydrofluoride, which solved the problem of single and high cost of tin source raw materials in the existing process, and achieved simplified process and efficient preparation. Nanofilms of different densities.

CN119320162AActive Publication Date: 2025-01-17GUANGZHOU INSTITUTE OF GEOCHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411385923.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-17
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In the existing preparation process of tin dioxide nanomaterials, the types of tin source raw materials are single, the cost is high, and the process is complex, so the synthesis process needs to be simplified to reduce costs.

Method used

Micron-scale tin dioxide powder crystals and potassium hydrofluoride are used as raw materials to synthesize tin dioxide nano films through high-temperature roasting and hydrolysis. The raw materials used are simple, the process is simplified, and the cost is reduced.

Benefits of technology

A tin dioxide nanofilm with different density was obtained, with small grain size, uniform distribution, and less agglomeration degree. It is suitable for different uses, such as molecular filter membranes, porous catalytic materials and battery materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005070978310000011
    Figure HDA0005070978310000011
  • Figure HDA0005070978310000012
    Figure HDA0005070978310000012
  • Figure HDA0005070978310000021
    Figure HDA0005070978310000021
Patent Text Reader

Abstract

The invention discloses a preparation method of a tin dioxide nano-film, which is characterized in that micron-sized tin dioxide powder crystals and potassium bifluoride are used as raw materials, and the tin dioxide nano-film is synthesized through a two-step method of high-temperature roasting and hydrolytic precipitation. The synthetic raw materials in the whole process are simple and easy to obtain, and the raw material cost is reduced; the synthesized tin dioxide nano-film has different densities, and the formed nano-particles are small in grain size, uniform in distribution and low in particle aggregation degree; the synthesis process is relatively simple, the reaction time is extremely short, the reaction temperature is low, the complex chemical process is avoided, and the process is relatively simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano multifunctional materials, and in particular relates to a method for preparing a tin dioxide (SnO2) nano film. Background Art

[0002] Tin dioxide (SnO2) is a wide bandgap semiconductor oxide. Due to its superior optical, electrical and catalytic properties, it is widely used in luminescent materials, light-absorbing materials, catalyst materials, gas-sensitive materials, rare-earth magnetic semiconductor materials, lithium-ion battery negative electrodes and other fields; and tin dioxide dopants can be used in conductive materials, thin-film resistors, solar cells, optoelectronic devices, reflectors, sensitive materials, fluorescent materials, fluorescent lamps and electrode materials. Nano-tin dioxide has unique small size effect, quantum size effect and surface effect, with extremely high specific surface area, and many surface oxygen defects and low oxygen coordination number, which is conducive to the generation of electronic carriers, thus having a relatively high carrier concentration. Therefore, tin dioxide has a wide range of application prospects in lithium-ion batteries, gas sensors, sensitized solar cells, catalysts, ultraviolet detection and other aspects.

[0003] In recent years, a large number of scholars are focusing on the research of new preparation methods of nano-tin dioxide, including: hydrothermal method, chemical vapor deposition method, physical vapor deposition method, sol-gel method, electrostatic spinning method, carbon thermal reduction method, high-temperature self-propagating synthesis method, pulsed laser deposition method, spray thermal bonding method, etc. Various methods have successfully prepared tin dioxide nanomaterials with different morphological characteristics, such as nanospheres, nanorods, nanobelts, nanosheets, nanosphere flowers, hollow microspheres, nanofibers, nanotube arrays and nano-mesopores, etc.

[0004] In the above synthesis methods, various raw materials and reagents such as tin raw materials + precipitant ± stabilizer ± solvent are basically used. At present, the most widely used tin raw materials are mainly tin chloride pentahydrate (SnCl4·5H2O), followed by stannous chloride dihydrate (SnCl2·2H2O), tin chloride (SnCl4), tin nitrate pentahydrate (Sn(NO3)4·5H2O), sodium stannate (Na2SnO3), potassium stannate (K2SnO3), tin oxide (SnO2), tetraethyl tin (Sn(C2H5)) and monobutyl tin trichloride, etc., and some inorganic or organic reagents are used as precipitants (such as urea, ammonia water, potassium hydroxide, sodium hydroxide, etc.), and some organic reagents are used as solvents or co-surfactants (such as ethanol, hydrogen peroxide, cyclohexane, ethylene glycol, etc.). Therefore, in the traditional process of synthesizing tin dioxide nanopowder, the types of tin source raw materials used are relatively single, and new high-quality and cheap tin source raw materials need to be further developed; at the same time, a variety of inorganic and organic reagents are used in the traditional process, some of which are relatively rare and expensive, which increases the synthesis cost and makes the synthesis process too complicated. It is also urgent to simplify the synthesis process to reduce the synthesis cost. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a tin dioxide nanofilm. The method uses micron-sized tin dioxide powder crystals and potassium bifluoride as raw materials, and synthesizes the tin dioxide nanofilm by a two-step method of high-temperature roasting and subsequent hydrolysis. The synthesized tin dioxide nanofilm has different densities, and the composed nanoparticles have small grain size, uniform distribution, and less particle agglomeration.

[0006] The above-mentioned object of the present invention can be achieved by the following technical scheme: A method for preparing a tin dioxide nanofilm comprises the following steps:

[0007] (1) Using tin dioxide and potassium bifluoride powder as initial raw materials, the two raw materials are placed in a container and covered, and the container is heated, and the heating temperature is adjusted to 300-400° C., and the heating time is 0.3-1.0 hour, so that the solid powder undergoes a sufficient melting reaction, and after the reaction, the container is cooled, and a dilute hydrofluoric acid solution is added to the container, and the container is heated to boiling again, and the container is continuously stirred to completely dissolve the solid in the container, and the heating is stopped;

[0008] (2) filtering the solution in the container while hot and collecting the filtrate;

[0009] (3) adding deionized water to the filtrate of step (2) to prepare a dilute solution, placing the dilute solution in a hydrothermal reaction container, sealing the hydrothermal reaction container, heating the hydrothermal reaction container, adjusting the temperature in the hydrothermal reaction container to 150-500° C., adjusting the pressure in the hydrothermal reaction container to 10-100 MPa by injecting inert gas into the hydrothermal reaction container, reacting for 8-48 hours, and rapidly cooling to room temperature after the reaction;

[0010] (4) Open the hydrothermal reaction vessel and obtain a tin dioxide nanofilm through subsequent treatment.

[0011] The present invention uses micron-sized tin dioxide powder crystals and potassium bifluoride as raw materials, and synthesizes tin dioxide nanofilms by a two-step method of high-temperature roasting and hydrolysis precipitation. The entire process uses only four inorganic reagents, tin dioxide, potassium bifluoride, hydrofluoric acid and ethanol. The synthetic raw materials are simple and easy to obtain, which reduces the cost of raw materials; the synthesized tin dioxide nanofilm has different densities, and the composed nanoparticles have small grain sizes, uniform distribution, and less particle agglomeration; the synthesis process is relatively simple, the reaction time is extremely short, the reaction temperature is low, and complex chemical processes are avoided, and the process is relatively simplified.

[0012] In the preparation method of the above-mentioned tin dioxide nanofilm:

[0013] More preferably, in step (1), tin dioxide and potassium bifluoride powder are used as initial raw materials, the two raw materials are placed in a container and covered, and the container is heated, the heating temperature is adjusted to 350° C., and the heating time is 0.5 hour, so that the solid powder undergoes a sufficient melting reaction.

[0014] Optionally, the mass ratio of tin dioxide to potassium bifluoride in step (1) is 1:2-3.

[0015] Optionally, the volume percentage of the dilute hydrofluoric acid solution in step (1) is 3-8%, preferably 5%, and the amount added is 40-60%, preferably 50% of the total volume of the container.

[0016] Optionally, the container in step (1) is a crucible, and the crucible is a hafnium alloy, or the crucible is a crucible lined with silver, gold or platinum.

[0017] Optionally, in step (1), a Teflon stirring rod is used for stirring.

[0018] Optionally, in step (2), an evaporating dish lined with Teflon, silver, gold or platinum is used to collect the filtrate.

[0019] Optionally, the filtration in step (2) is repeated 3 to 5 times.

[0020] Optionally, the molar concentration of the dilute solution in step (3) is 0.01 to 0.05 mol / L.

[0021] Optionally, the inert gas in step (3) is argon or helium.

[0022] More preferably, the reaction temperature in step (3) is 200-450°C.

[0023] Optionally, the reaction time described in step (3) includes the time consumed for heating.

[0024] Optionally, the rapid cooling in step (3) is to use ice water or compressed air to quickly cool the reactor.

[0025] As one of the preferred technical solutions of the present invention, in step (3), the dilute solution is directly added to the hydrothermal reaction vessel, and the volume of the dilute solution accounts for 30-70% of the total volume of the hydrothermal reaction vessel; the hydrothermal reaction vessel is a hydrothermal reaction kettle, and the hydrothermal reaction kettle is a sealed high-temperature and high-pressure reaction kettle, and the high-temperature and high-pressure reaction kettle is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reaction kettle has a metal shell, and the metal shell is provided with a strong acid and strong alkali resistant lining, and the strong acid and strong alkali resistant lining is polytetrafluoroethylene, polyphenyl ester, polyimide plastic, or the strong acid and strong alkali resistant lining is silver, gold or platinum inert metal, or the strong acid and strong alkali resistant lining is gold palladium or silver palladium alloy.

[0026] Optionally, the hydrothermal reaction vessel is a conventional commercially available hydrothermal reaction vessel, the sealed high-temperature and high-pressure reactor is a conventional commercially available sealed high-temperature and high-pressure reactor, and the metal in the metal shell is conventional stainless steel or Hastelloy.

[0027] When adopting this technical solution, optionally, in step (4), the hydrothermal reaction container is opened, and the subsequent treatment to obtain the tin dioxide nanofilm includes: opening the hydrothermal reaction container, recovering the residual solution in the hydrothermal reaction container, washing the inner wall of the hydrothermal reaction container with deionized water, collecting the washed fluid to obtain a nano-tin dioxide turbid liquid, centrifuging the obtained turbid liquid, removing the lower layer of precipitate, and washing and drying the lower layer of precipitate to obtain the tin dioxide nanofilm.

[0028] When adopting this technical solution, optionally, a sample collection sheet is provided at the bottom of the hydrothermal reaction container in step (3), and the sample collection sheet is a sample collection sheet made of plastic or inert metal; in step (4), the hydrothermal reaction container is opened, and the tin dioxide nanofilm is obtained through subsequent treatment, including: opening the hydrothermal reaction container, recovering the residual solution in the hydrothermal reaction container, taking out the sample collection sheet, washing and drying, and obtaining the tin dioxide nanofilm on the surface of the sample collection sheet.

[0029] Optionally, the plastic is polytetrafluoroethylene, polyphenylene ester or polyimide, etc.; the inert metal material is silver, gold or platinum, etc.

[0030] Optionally, the cleaning or washing is performed by washing with deionized water and anhydrous ethanol 2 to 3 times in sequence.

[0031] Optionally, the drying is natural air drying or storage in a desiccating dish.

[0032] As another preferred technical solution of the present invention, in step (3), the dilute solution is first added to a precious metal vessel, and then the precious metal vessel is placed in a hydrothermal reaction vessel, the precious metal is silver, gold or platinum; or the precious metal is gold-palladium or silver-palladium alloy; the high-temperature and high-pressure reactor is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reactor has a stainless steel or Hastelloy metal shell.

[0033] When adopting this technical solution, optionally, in step (4), the hydrothermal reaction vessel is opened, and the subsequent treatment to obtain the tin dioxide nanofilm includes: opening the hydrothermal reactor, taking out the precious metal container, recovering the residual solution in the precious metal container, washing the inner wall of the precious metal container with deionized water, collecting the washed fluid to obtain a nano-tin dioxide turbid liquid, centrifuging the obtained turbid liquid, removing the lower layer of precipitate, and washing and drying the lower layer of precipitate to obtain the tin dioxide nanofilm.

[0034] Optionally, the cleaning is performed by washing with deionized water and anhydrous ethanol 2 to 3 times in sequence.

[0035] Optionally, the drying is natural air drying or storage in a desiccating dish.

[0036] The core of the tin dioxide nanofilm preparation method of the present invention is to introduce fluorine and promote the formation of tetragonal tin dioxide by using a two-step method of high-temperature calcination and hydrolysis of tin dioxide and potassium bifluoride. The presence of fluorine can promote the development of multiple crystal faces such as (101) and (211) of tin dioxide nanocrystals, and help the connection growth of tin dioxide nanocrystals during the hydrolysis process, thereby improving the density of the tin dioxide film.

[0037] In the method for preparing the tin dioxide nanofilm of the present invention, the core reagents used are common and inexpensive tin dioxide and potassium bifluoride reagents, which avoids the complex process of using multiple raw materials such as tin source + precipitant ± surfactant ± solvent in the traditional process. Since the type and crystal shape of the nanocrystals are controlled by temperature and pressure in step (3) of the present invention, the degree of hydrolysis reaction and the size of the tin dioxide nanocrystals are controlled by reaction time.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The preparation method of the present invention uses common and inexpensive micron-sized tin dioxide powder and potassium bifluoride as raw materials for the first time, and generates tetragonal tin dioxide nanocrystals by a two-step method of high-temperature calcination and subsequent hydrolysis, which is then grown into a nanofilm, thereby realizing the preparation of tin dioxide nanofilms using simple common reagents, and expanding the synthesis process of tin dioxide nanocrystals;

[0040] (2) The preparation method of the present invention inherits the advantages of the traditional hydrothermal liquid phase synthesis process, and the whole synthesis process only needs to use four common and inexpensive reagent raw materials, namely tin dioxide, potassium bifluoride, hydrofluoric acid and ethanol, avoiding the proportioning and weighing of multiple expensive precursors, precipitants, surface area enhancers and solvents and other morphology control agents in the traditional process, as well as the sequential process steps. Therefore, the method is simple in process, easy to operate and control, and has low cost;

[0041] (3) The preparation method of the present invention uses common and inexpensive tin dioxide and potassium bifluoride reagents to synthesize tin dioxide nanofilms with different densities through a two-step method. The nanofilms with different densities can be used for different purposes according to the size of the gaps, such as molecular filtration membranes, porous catalytic materials, battery materials, and material protection layers, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The scanning electron microscope photos (a, b) of the tin dioxide nanofilm prepared in Example 1 of the present invention at different magnifications, wherein (a) is magnified 80,000 times, and (b) is magnified 50,000 times;

[0043] Figure 2 The scanning electron microscope photographs (ad) of the tin dioxide nanofilm prepared in Example 2 of the present invention at different magnifications, wherein (a) is magnified 50,000 times, (b) is magnified 35,000 times, (c) is magnified 20,000 times, and (d) is magnified 20,000 times;

[0044] Figure 3 The scanning electron microscope photos (a, b) of the tin dioxide nanofilm prepared in Example 3 of the present invention at different magnifications, wherein (a) is magnified 20,000 times, and (b) is magnified 35,000 times;

[0045] Figure 4 The scanning electron microscope photographs (ad) of the tin dioxide nanofilm prepared in Example 4 of the present invention at different magnifications, wherein (a) is magnified 20,000 times, (b) is magnified 30,000 times, (c) is magnified 50,000 times, and (d) is magnified 50,000 times;

[0046] Figure 5 The scanning electron microscope photos (a, b) of the tin dioxide nanofilm prepared in Example 5 of the present invention at different magnifications, wherein (a) is magnified 10,000 times, and (b) is magnified 40,000 times;

[0047] Figure 6 The scanning electron microscope photos (a, b) of the tin dioxide nanofilm prepared in Example 6 of the present invention at different magnifications, wherein (a) is magnified 35,000 times, and (b) is magnified 40,000 times;

[0048] Figure 7The scanning electron microscope photos (a, b) of the tin dioxide nanofilm prepared in Example 7 of the present invention at different magnifications, wherein (a) is magnified 35,000 times, and (b) is magnified 20,000 times;

[0049] Figure 8 The scanning electron microscope photographs (ad) of the tin dioxide nanofilm prepared in Example 8 of the present invention at different magnifications, wherein (a) is magnified 20,000 times, (b) is magnified 30,000 times, (c) is magnified 50,000 times, and (d) is magnified 60,000 times;

[0050] Fig. 9 The scanning electron microscope photos (ad) of the tin dioxide nanofilm prepared in Example 9 of the present invention at different magnifications, wherein (a) is magnified 15,000 times, (b) is magnified 12,000 times, (c) is magnified 50,000 times, and (d) is magnified 22,000 times;

[0051] Fig.10 This is a comparison diagram of the laser Raman spectra of the tin dioxide nanofilm prepared in Examples 1-9 of the present invention and a standard tin dioxide crystal;

[0052] Fig.11 It is the μ-XRD spectrum of the tin dioxide nanofilm prepared in the embodiment of the present invention. Since the tin dioxide nanofilm is deposited on a gold sheet, the gold spectrum appears in the XRD background. The upper figure is the μ-XRD spectrum obtained under low temperature conditions in Example 1; the middle figure is the μ-XRD spectrum obtained under high temperature conditions in Example 3; the lower figure is the μ-XRD spectrum obtained under high temperature conditions in Example 9, wherein the ordinate Intensity (Counts) is the count, and the abscissa Two-Theta (deg) is the diffraction angle. DETAILED DESCRIPTION

[0053] The present invention is further described below in conjunction with specific examples. The following examples are only for illustrative purposes and should not be construed as limiting the present invention. Unless otherwise specified, the raw materials used in the following examples are conventional commercially available or commercially available raw materials, and unless otherwise specified, the methods and equipment used in the following examples are conventional methods and equipment used in the art. The hydrothermal reactor is a conventional hydrothermal reactor, and its material is mostly stainless steel or Hastelloy. Anything not explicitly specified in the synthesis method is a conventional operation or conventional device.

[0054] The present invention is further described below in conjunction with examples and drawings, but the scope of protection claimed by the present invention, such as the reaction device, reaction temperature, reaction time and volume of the reaction liquid, is not limited to those in the examples.

[0055] Example 1

[0056] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0057] (1) 2.00 g of tin dioxide (SnO2, 99.99% purity, Aladdin, the same below, micron-sized powder crystal) and 6.00 g of potassium hydrogen fluoride (KHF, 99% purity, Aladdin, the same below) powder are placed in a silver crucible and covered with a lid. A platinum crucible is placed on an electric furnace and the temperature of the electric furnace is set to 350° C. The crucible is heated for half an hour. After cooling slightly, the crucible lid is opened and 5% (volume percentage) hydrofluoric acid is added to the crucible until it reaches half the volume of the crucible. The electric furnace is continued to be turned on to heat until boiling. A Teflon rod is used to stir continuously to completely dissolve the solid in the crucible and stop heating.

[0058] (2) Pour the solution in the crucible onto filter paper while it is hot and filter it. Use a silver evaporating dish to receive the filtrate. Repeat the filtration three times. Use 100 mL of deionized water to dilute the filtrate to 0.01 mol / L to obtain a reaction solution. Put the obtained reaction solution into a 200 mL hydrothermal reactor. The hydrothermal reactor is a sealed high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor is connected to a high-precision ultra-high pressure pressure gauge, a ventilation pipe and a stop valve. The high-temperature and high-pressure reactor has a stainless steel metal shell, and a polytetrafluoroethylene liner is provided in the metal shell. After tightening the reactor, argon gas is injected into the reactor through the ventilation pipe to a pressure of 40 MPa, and the stop valve is closed to stop gas injection. The reactor is heated by a heating furnace, and the reaction temperature is set to 200° C. After the temperature rises to 200° C., the stop valve is opened, and argon gas is continuously injected to a pressure of 60 MPa. The reaction time is maintained for 22.5 hours. After the reaction is completed, ice water is used to pour the reactor to quickly cool it to room temperature;

[0059] (3) Open the reactor, recover the residual solution in the reactor, wash the inner wall of the reactor with deionized water, collect the washed fluid to obtain a nano-tin dioxide turbid liquid, place the obtained turbid liquid in a centrifuge for centrifugation, take out the lower precipitate after centrifugation, and rinse it with deionized water and anhydrous ethanol 2 to 3 times, and finally air-dry the precipitate to obtain a low-density tin dioxide nanofilm.

[0060] Figure 1 Figures (a) and (b) show the morphology and particle size of the tin dioxide nanoparticles that make up the tin dioxide nanofilm at different magnifications. It can be seen that the nanoparticles are rice-grain-shaped, with a particle size of several nanometers to 100 nanometers.

[0061] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the SnO2 nanoparticles in the SnO2 film synthesized at 200°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single SnO2 crystal, namely 474 cm -1 、634cm-1 and 775cm -1 , indicating that the synthesized rice-like nanoparticles are basically tin dioxide.

[0062] Fig.11 The μ-XRD analysis in the figure shows that the SnO2 nanoparticles in the SnO2 film synthesized at 200°C are tetragonal in structure, with only (101) and (211) faces developed, while other crystal faces are not developed.

[0063] Example 2

[0064] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0065] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a dilute solution with a concentration of 0.01 mol / L. 5 mL of the prepared dilute solution was placed in a gold tube with a diameter of 4.5 mm and then sealed by welding. The gold tube was then placed in the high-temperature and high-pressure reactor in Example 1. After tightening the reactor, argon gas was injected into the reactor through the ventilation pipe to a pressure of 80 MPa. The stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace and the reaction temperature was set to 250° C. After the temperature rose to 250° C., the stop valve was opened and argon gas was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 22.5 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature.

[0066] (2) The reaction kettle in step (1) is opened, the gold tube is taken out and broken, the residual solution is recovered, the inner wall of the gold tube is washed with deionized water, and the washed fluid is collected to obtain a nano-tin dioxide turbid liquid, and the obtained turbid liquid is placed in a centrifuge for centrifugation. After the centrifugation, the lower layer of precipitate is taken out and rinsed with deionized water and anhydrous ethanol 2 to 3 times, and finally the precipitate is naturally air-dried to obtain a high-density tin dioxide nanofilm.

[0067] Figure 2 Figures (a) to (d) show the morphology and particle size of tin dioxide nanopowder at different magnifications. It can be seen that the nanoparticles are rice-grain and pyramidal, with a particle size of several nanometers to 100 nanometers. Tin dioxide nanocrystals are tightly connected into a dense nanolayer film. Figure 2 The middle figure (c) shows a longitudinal cross-section of the nanolayer film, which is an array of nanoparticles composed of nanocrystals. The nanofilm is of uniform thickness and is about 100 nanometers thick.

[0068] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the SnO2 nanopowder in the SnO2 film synthesized at 250°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single SnO2 crystal, namely 474cm -1、634cm -1 and 775cm -1 , indicating that the synthesized nanopowders are all tin dioxide.

[0069] Example 3

[0070] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0071] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a dilute solution with a concentration of 0.01 mol / L. The dilute solution was placed in a hydrothermal reactor, and a flat gold sheet was placed at the bottom of the reactor. After tightening the reactor, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa, and the stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace and the reaction temperature was set to 450° C. After the temperature rose to 450° C., the stop valve was opened, and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 22.5 hours. After the reaction was completed, ice water was used to quickly cool the reactor to room temperature.

[0072] (2) The reaction kettle in step (1) is opened, the residual solution in the kettle is recovered, the gold flakes in the kettle are taken out, and they are washed 2 to 3 times with deionized water and anhydrous ethanol. After natural air drying, a layer of nano-tin dioxide film can be seen on the surface of the gold flakes.

[0073] Figure 3 Figures (a) and (b) in the middle show scanning electron microscope photos of tin dioxide nanoparticles in tin dioxide films at different magnifications, showing that the nanoparticles are uniform, mainly rice-grain and pyramidal in shape, with a particle size of several nanometers to about 100 nanometers, and the tin dioxide nanocrystals are tightly connected into a dense nanolayer film.

[0074] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the SnO2 nanoparticles in the SnO2 film synthesized at 450°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single SnO2 crystal, namely 474 cm -1 、634cm -1 and 775cm -1 , indicating that the synthesized nanoparticles are all tin dioxide.

[0075] Fig.11 The μ-XRD analysis in the figure shows that the tin dioxide nanoparticles in the tin dioxide film synthesized at 450°C are tetragonal in structure and have euhedral crystal forms with multiple crystal planes such as (110), (101), (211), (220), (310), (320), (321), (222), and (312).

[0076] Example 4

[0077] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0078] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a dilute solution with a concentration of 0.02 mol / L, and the dilute solution was placed in a 200 mL hydrothermal reactor. The hydrothermal reactor was a sealed high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve. The high-temperature and high-pressure reactor had a metal shell, and a polytetrafluoroethylene liner was provided in the metal shell. After the reactor was tightened, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa, the stop valve was closed to stop the gas injection, and the reactor was heated by a heating furnace, and the reaction temperature was set to 200° C. After the temperature rose to 200° C., the stop valve was opened, and argon was continuously injected to a pressure of 100 MPa, and the reaction time was maintained for 37 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature;

[0079] (2) The reaction kettle in step (1) is opened, the residual solution in the kettle is recovered, the inner wall of the kettle is washed with deionized water, and the washed fluid is collected to obtain a nano-tin dioxide turbid liquid, which is placed in a centrifuge for centrifugation. After the centrifugation, the lower layer of precipitate is taken out and rinsed with deionized water and anhydrous ethanol 2 to 3 times, and finally the precipitate is naturally air-dried to obtain a high-density tin dioxide nanofilm.

[0080] Figure 4 Figures (a) to (d) show the morphology and particle size of tin dioxide nanoparticles in the tin dioxide nanofilm at different magnifications. It can be seen that the nanoparticles are rice-grain and pyramidal in shape, with a particle size ranging from a few nanometers to 200 nanometers.

[0081] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the tin dioxide particles in the tin dioxide nanofilm synthesized at 200°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single tin dioxide crystal, namely 474 cm -1 、634cm -1 and 775cm -1 , indicating that the synthesized rice-like nanopowders are basically tin dioxide.

[0082] Example 5

[0083] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0084] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a dilute solution with a concentration of 0.02 mol / L. The dilute solution was placed in a hydrothermal reactor, and a flat gold sheet was placed at the bottom of the reactor. After tightening the reactor, argon was injected into the reactor through a ventilation pipe to a pressure of 80 MPa, and the stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace, and the reaction temperature was set to 300° C. After the temperature rose to 300° C., the stop valve was opened, and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 23 hours. After the reaction was completed, ice water was used to quickly cool the reactor to room temperature.

[0085] (2) The reaction kettle in step (1) is opened, the residual solution in the kettle is recovered, the gold flakes in the kettle in step (1) are taken out, and they are washed 2 to 3 times with deionized water. After natural air drying, a layer of nano-tin dioxide film can be seen on the surface of the gold flakes.

[0086] Figure 5 Figures (a) and (b) in the middle show scanning electron microscope photos of tin dioxide nanoparticles in tin dioxide films at different magnifications, showing that the nanoparticles are uniform, mainly irregular pyramidal shapes, with particle sizes ranging from tens of nanometers to about 300 nanometers, and the tin dioxide nanoparticles are tightly connected into a dense nanolayer film.

[0087] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the SnO2 nanoparticles in the SnO2 film synthesized at 300°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single SnO2 crystal, namely 474 cm -1 、634cm -1 and 775cm -1 , indicating that the synthesized nanopowders are all tin dioxide.

[0088] Example 6

[0089] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0090] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a dilute solution with a concentration of 0.05 mol / L, and the dilute solution was placed in a 200 mL hydrothermal reactor. The hydrothermal reactor was a sealed high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve. The high-temperature and high-pressure reactor had a metal shell, and a polytetrafluoroethylene liner was provided in the metal shell. After tightening the reactor, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa, and the stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace, and the reaction temperature was set to 200° C. After the temperature rose to 200° C., the stop valve was opened, and argon was continuously injected to a pressure of 100 MPa, and the reaction time was maintained for 8 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature;

[0091] (2) The reaction kettle in step (1) is opened, the residual solution in the kettle is recovered, the inner wall of the kettle is washed with deionized water, and the washed fluid is collected to obtain a nano-tin dioxide turbid liquid, which is placed in a centrifuge for centrifugation. After the centrifugation, the lower layer of precipitate is taken out and rinsed with deionized water and anhydrous ethanol 2 to 3 times, and finally the precipitate is naturally air-dried to obtain a low-density tin dioxide nanofilm.

[0092] Figure 6 Figures (a) and (b) show the morphology and particle size of tin dioxide nanoparticles in the tin dioxide film at different magnifications. It can be seen that the nanoparticles are rice-grain-shaped with a particle size of tens of nanometers to 200 nanometers.

[0093] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the SnO2 nanoparticles in the SnO2 film synthesized at 200°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single SnO2 crystal, namely 474 cm -1 、634cm -1 and 775cm -1 , indicating that the synthesized rice-like nanoparticles are basically tin dioxide.

[0094] Example 7

[0095] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0096] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a dilute solution with a concentration of 0.05 mol / L. 5 mL of the dilute solution was placed in a gold tube with a diameter of 4.5 mm and then sealed by welding. The gold tube was then placed in a high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected to a high-precision ultra-high pressure pressure gauge, a ventilation pipe and a stop valve. The high-temperature and high-pressure reactor had a metal shell. After the reactor was tightened, argon gas was injected into the reactor through the ventilation pipe to a pressure of 80 MPa. The stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace and the reaction temperature was set to 200° C. After the temperature rose to 200° C., the stop valve in step (1) was opened, and argon gas was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 48 hours. After the reaction was completed, ice water was used to pour the reactor in step (1) to quickly cool it to room temperature.

[0097] (2) The reaction kettle in step (1) is opened, the gold tube is taken out and broken open, the residual solution is recovered, the inner wall of the gold tube is washed with deionized water, and the washed fluid is collected to obtain a nano-tin dioxide turbid liquid, and the obtained turbid liquid is placed in a centrifuge for centrifugation. After the centrifugation, the lower layer of precipitate is taken out and rinsed with deionized water and anhydrous ethanol 2 to 3 times, and finally the precipitate is naturally air-dried to obtain a low-density tin dioxide nanofilm.

[0098] Figure 7 Figures (a) and (b) show the morphology and particle size of tin dioxide nanoparticles in the tin dioxide film at different magnifications. It can be seen that the nanoparticles are rice-grain-shaped with a particle size of tens of nanometers to 500 nanometers.

[0099] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the tin dioxide particles in the tin dioxide nanofilm synthesized at 200°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single tin dioxide crystal, namely 474 cm -1 、634cm -1 and 775cm -1 , indicating that the synthesized rice-like nanoparticles are basically tin dioxide.

[0100] Example 8

[0101] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0102] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a dilute solution with a concentration of 0.05 mol / L. The dilute solution was placed in a hydrothermal reactor, and a flat gold sheet was placed at the bottom of the reactor. After the reactor was tightened, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa, and the stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace and the reaction temperature was set to 300° C. After the temperature rose to 300° C., the stop valve was opened, and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 14 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature.

[0103] (2) The reaction kettle in step (1) is opened, the residual solution in the kettle is recovered, the gold flakes in the reaction kettle are taken out, and they are washed 2 to 3 times with deionized water. After natural air drying, a layer of nano-tin dioxide film can be seen on the surface of the gold flakes.

[0104] Figure 8 Figures (a) and (b) in the middle show scanning electron microscope photos of tin dioxide nanoparticles in tin dioxide films at different magnifications, showing that the nanoparticles are uniform, mainly irregular pyramidal shapes, with particle sizes ranging from tens of nanometers to about 300 nanometers, and the tin dioxide nanoparticles are tightly connected into a dense nanolayer film.

[0105] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the SnO2 nanoparticles in the SnO2 film synthesized at 300°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single SnO2 crystal, namely 474 cm -1 、634cm -1 and 775cm -1 , indicating that the synthesized nanoparticles are all tin dioxide.

[0106] Example 9

[0107] The method for preparing the tin dioxide nanofilm provided in this embodiment comprises the following steps:

[0108] (1) 100 mL of deionized water was added to the filtrate prepared in step (1) of Example 1 to fully dissolve the filtrate to obtain a 0.05 mol / L reaction solution, and the obtained reaction solution was placed in a hydrothermal reactor. A flat gold sheet was placed at the bottom of the reactor. After the reactor was tightened, argon was injected into the reactor through a ventilation pipe to a pressure of 80 MPa, and the stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace, and the reaction temperature was set to 500° C. After the temperature rose to 500° C., the stop valve was opened, and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 24 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature;

[0109] (2) The reaction kettle in step (1) is opened, the residual solution in the kettle is recovered, the gold flakes in the kettle in step (1) are taken out, and they are washed 2 to 3 times with deionized water. After natural air drying, a layer of nano-tin dioxide film can be seen on the surface of the gold flakes.

[0110] Fig. 9 Figures (a) and (b) in the middle show scanning electron microscope photos of tin dioxide nanofilms at different magnifications, showing that the nanoparticles are uneven in size, mainly irregular pyramidal and blocky, with particle sizes ranging from tens of nanometers to about 600 nanometers. The tin dioxide nanoparticles are tightly connected into a dense nanolayer film.

[0111] Fig.10 Laser Raman spectroscopy shows that the Raman scattering peaks of the SnO2 nanoparticles in the SnO2 film synthesized at 500°C are obvious, clearly indicating three Raman scattering peaks similar to those of the standard single SnO2 crystal, namely 474 cm -1 、634cm -1 and 775cm -1 , indicating that the synthesized nanoparticles are all tin dioxide.

[0112] Fig.11 The μ-XRD analysis in the figure shows that the tin dioxide nanoparticles in the tin dioxide nanofilm synthesized at 500°C are tetragonal in structure and have euhedral crystal forms with multiple crystal planes such as (110), (101), (211), (220), (310), (320), (321), (222), and (312).

[0113] The above embodiments are only used to illustrate the present invention, and the protection scope of the present invention is not limited to the above embodiments. A person skilled in the art can achieve the purpose of the present invention based on the above disclosure of the present invention, and any improvement and deformation based on the concept of the present invention shall fall within the protection scope of the present invention, and the specific protection scope shall be subject to the claims.

Claims

1. A method for preparing a tin dioxide nanofilm, characterized in that: The following steps are involved: (1) Using tin dioxide and potassium bifluoride powder as initial raw materials, the two raw materials are placed in a container and covered, and the container is heated, and the heating temperature is adjusted to 300-400° C., and the heating time is 0.3-1.0 hour, so that the solid powder undergoes a sufficient melting reaction, and after the reaction, the container is cooled, and a dilute hydrofluoric acid solution is added to the container, and the container is heated to boiling again, and the container is continuously stirred to completely dissolve the solid in the container, and the heating is stopped; (2) filtering the solution in the container while hot and collecting the filtrate; (3) adding deionized water to the filtrate of step (2) to prepare a dilute solution, placing the dilute solution in a hydrothermal reaction container, sealing the hydrothermal reaction container, heating the hydrothermal reaction container, adjusting the temperature in the hydrothermal reaction container to 150-500° C., adjusting the pressure in the hydrothermal reaction container to 10-100 MPa by injecting inert gas into the hydrothermal reaction container, reacting for 8-48 hours, and rapidly cooling to room temperature after the reaction; (4) Open the hydrothermal reaction vessel and obtain a tin dioxide nanofilm through subsequent treatment.

2. The method for preparing the tin dioxide nanofilm according to claim 1, characterized in that: The mass ratio of tin dioxide to potassium bifluoride in step (1) is 1:2-3.

3. The method for preparing the tin dioxide nanofilm according to claim 1, characterized in that: The volume percentage of the dilute hydrofluoric acid solution in step (1) is 3-8%, and the amount added is 40-60% of the total volume of the container; the container in step (1) is a crucible, and the crucible is a hafnium alloy, or the crucible is a crucible lined with silver, gold or platinum; and a Teflon stirring rod is used for stirring in step (1).

4. The method for preparing the tin dioxide nanofilm according to claim 1, characterized in that: In step (2), an evaporating dish lined with Teflon, silver, gold or platinum is used to collect the filtrate.

5. The method for preparing the tin dioxide nanofilm according to claim 1, characterized in that: The molar concentration of the dilute solution in step (3) is 0.01-0.05 mol / L; the inert gas in step (3) is argon or helium.

6. The method for preparing the tin dioxide nanofilm according to claim 1, characterized in that: In step (3), the dilute solution is directly added to the hydrothermal reaction vessel, and the volume of the dilute solution accounts for 30-70% of the total volume of the hydrothermal reaction vessel; the hydrothermal reaction vessel is a hydrothermal reaction kettle, and the hydrothermal reaction kettle is a sealed high-temperature and high-pressure reaction kettle, and the high-temperature and high-pressure reaction kettle is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reaction kettle has a metal shell, and the metal shell is provided with a strong acid and strong alkali resistant lining, and the strong acid and strong alkali resistant lining is polytetrafluoroethylene, polyphenyl ester, polyimide plastic, or the strong acid and strong alkali resistant lining is silver, gold or platinum inert metal, or the strong acid and strong alkali resistant lining is gold palladium, silver palladium alloy.

7. The method for preparing the tin dioxide nanofilm according to claim 6, characterized in that: The step (4) of opening the hydrothermal reaction vessel and obtaining the tin dioxide nanofilm through subsequent treatment includes: opening the hydrothermal reaction vessel, recovering the residual solution in the hydrothermal reaction vessel, washing the inner wall of the hydrothermal reaction vessel with deionized water, collecting the washed fluid to obtain a nano-tin dioxide turbid liquid, centrifuging the obtained turbid liquid, removing the lower layer of precipitate, and washing and drying the lower layer of precipitate to obtain the tin dioxide nanofilm; the residual solution mainly comprises potassium hexafluorostannate, hydrofluoric acid and potassium fluoride.

8. The method for preparing the tin dioxide nanofilm according to claim 6, characterized in that: In step (3), a sample collection sheet is provided at the bottom of the hydrothermal reaction container, and the sample collection sheet is a sample collection sheet made of plastic or inert metal. In step (4), the hydrothermal reaction container is opened, and the tin dioxide nanofilm is obtained through subsequent treatment, including: opening the hydrothermal reaction container, recovering the residual solution in the hydrothermal reaction container, taking out the sample collection sheet, washing and drying, and then obtaining the tin dioxide nanofilm on the surface of the sample collection sheet; the residual solution mainly comprises potassium hexafluorostannate, hydrofluoric acid and potassium fluoride.

9. The method for preparing a tin dioxide nanofilm according to claim 1, characterized in that: In step (3), a dilute potassium hexafluorostannate solution is first added to a precious metal vessel, and then the precious metal vessel is placed in a hydrothermal reaction vessel, wherein the precious metal is silver, gold or platinum; or the precious metal is gold-palladium or silver-palladium alloy; the high-temperature and high-pressure reactor is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reactor has a metal shell.

10. The method for preparing a tin dioxide nanofilm according to claim 9, characterized in that: In step (4), the hydrothermal reaction vessel is opened, and the subsequent treatment to obtain the tin dioxide nanofilm includes: opening the hydrothermal reactor, taking out the precious metal container, recovering the residual solution in the precious metal container, washing the inner wall of the precious metal container with deionized water, collecting the washed fluid to obtain a nano-tin dioxide turbid liquid, centrifuging the obtained turbid liquid, removing the lower layer of precipitate, and washing and drying the lower layer of precipitate to obtain the tin dioxide nanofilm.

Citation Information

Patent Citations

  • Zirconium dioxide nanosphere with uniform particle size, film of zirconium dioxide nanosphere and preparation method of zirconium dioxide nanosphere and film thereof

    CN110217818A